2008
DOI: 10.1096/fj.07-098038
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, a major defense protein of innate immunity, is a novel maturation factor for human dendritic cells

Abstract: Lactoferrin (LF) is an important protein component of the innate immune system that is broadly distributed within the body fluids. LF is endowed with multiple biological activities. Talactoferrin (TLF), a recombinant human LF, is in clinical development as an anticancer agent and is entering Phase III clinical trials. Here, we show that TLF induces the maturation of human dendritic cells (DCs) derived from monocytes. TLF, at physiologically relevant concentrations (100 microg/ml) up-regulates the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 55 publications
5
98
0
Order By: Relevance
“…Lf is present in mucosal tissues and in most bodily fluids, such as milk, tear fluid, saliva, nasal secretions and vaginal mucus, and at low concentration in serum (Masson et al, 1966;Weinberg, 2001). Lf is of interest with regard to DCs as it can interact directly with these cells and modulate important functions such as migration, cell activation and induction of T-cell responses (de la Rosa et al, 2008;Puddu et al, 2009;Spadaro et al, 2008). It is therefore likely that Lf is present at high concentration at anatomical sites where peripheral DCs encounter pathogens such as Ad5 in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lf is present in mucosal tissues and in most bodily fluids, such as milk, tear fluid, saliva, nasal secretions and vaginal mucus, and at low concentration in serum (Masson et al, 1966;Weinberg, 2001). Lf is of interest with regard to DCs as it can interact directly with these cells and modulate important functions such as migration, cell activation and induction of T-cell responses (de la Rosa et al, 2008;Puddu et al, 2009;Spadaro et al, 2008). It is therefore likely that Lf is present at high concentration at anatomical sites where peripheral DCs encounter pathogens such as Ad5 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lf is mainly known for its immunomodulatory properties, which enhance anti-microbial and anti-inflammatory responses (Legrand et al, 2005). High levels of Lf present during inflammation were recently shown to directly recruit and activate DCs (de la Rosa et al, 2008;Spadaro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2 The diverse list of LF's multifunctional roles includes immunomodulatory, anticancer, antibacterial, and antiviral properties. 3,4 Some of the recent studies have demonstrated LF as an effector molecule in the skeleton, 5,6 due to its ability to increase osteoblast proliferation, survival, and differentiation [6][7][8] and decrease osteoclast survival. 9,10 Many of the biological activities of LF have been attributed to its ability to induce signal transduction pathways through cell surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Negative data emerged also from clinical trials with PF-3512676, a synthetic TLR9-activating oligodeoxynucleotide, which works as the natural ligand of TLR9 which enhances maturation of DCs [72,73]. Also, lactoferrin, which is an iron-binding glycoprotein found in breast milk, has shown several immunomodulatory functions [74]. Talactoferrin-a is the recombinant human variant of lactoferrin, purified from Aspergillus niger var.…”
Section: Ganglioside Vaccines: Racotumomabmentioning
confidence: 99%